H.D., modernist fiction, and a queer quotidian. Issue 2 (4th May 2022) - Vetter, Lara
ABSTRACT: This article proposes that H.D. imagines the possibilities of a queer quotidian in two short stories, "Narthex" and "The Usual Star, " written in the late 1920s. The queer quotidian is registered not just at the level of content but of form, and in ways that problematize high modernist aesthetics. In these stories, H.D. ironizes epiphany, critiques stream of consciousness, and explores the limitations of various narrative points of view and styles, suggesting that the self is a fiction and that perspective is inevitably a function of desire. Ultimately, the queer quotidian is ephemeral, to be experienced only in moments.